Failure analysis of engineering materials / Charlie R. Brooks and Ashok Choudhury. - Brooks, Charlie R. (McGraw-Hill, 2001)
This is a single point reference for fracture and failure anaylsis of metals, ceramics, plastics, composites and electronic materials in engineering applications.